2019
DOI: 10.1002/asia.201900607
|View full text |Cite
|
Sign up to set email alerts
|

Halogen‐Bonding‐Induced Conjugate Addition of Thiophenes to Enones and Enals

Abstract: Herein, we report the conjugate addition of a,bunsaturated carbonyl compounds to thiophene derivatives. We used a2 -iodoimidazolinium triflate salt as ah alogenbonding donor,w hich afforded moderate-to-excellent yields of the corresponding alkylated thiophenes. Insight into the catalytic process was obtained from 1 HNMR spectroscopy studies and DFT calculations, which indicated ah alogenbonding-supportedm echanism with limited Brønsted acid catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Thirdly, comparison to other possible pathways is highly desirable, especially to the Brønsted acid pathway. It was noted experimentally and theoretically by Breugst et al [81], Scheidt et al [28], and our group [43,92] that the Brønsted acid catalysis pathway is competitive or superior to the XB catalysis pathway for the investigated reactions. However, the understanding of how a trace amount of acid could be generated is quite limited, perhaps because there are not many experimental reports, if any, of such a nature.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thirdly, comparison to other possible pathways is highly desirable, especially to the Brønsted acid pathway. It was noted experimentally and theoretically by Breugst et al [81], Scheidt et al [28], and our group [43,92] that the Brønsted acid catalysis pathway is competitive or superior to the XB catalysis pathway for the investigated reactions. However, the understanding of how a trace amount of acid could be generated is quite limited, perhaps because there are not many experimental reports, if any, of such a nature.…”
Section: Discussionmentioning
confidence: 57%
“…Tan et al reported an XB-catalyzed conjugate addition of thiophenes to enones and enals [92]. A bidentate imidazolinium-based catalyst (47) was found to be the most active catalysts tested.…”
Section: Xb-catalyzed Conjugate Addition Of Thiophenes To Enones and mentioning
confidence: 99%
“…As can be seen, this base had no noticeable effect on the chemical shift of the protons of interest, but addition of ever increasing amounts of 22 clearly shifted the protons downfield, which is evidence for a halogen bonding interaction between 9 a and 22 [10a] . This notion is supported by the observation that the protons of the methyl groups of 9 a likewise exhibited a similar downfield shift in the presence increasing amounts of 22 (Figure 4b) [37] . It should be noted that similar trends were observed when of mixtures of 13 a and 9 a were studied (Figure SI‐1), that indicate that 9 a can also interact with the oxygen atom of the furan substrates.…”
Section: Figurementioning
confidence: 54%
“…Since halogen bond‐catalyzed Friedel−Crafts reactions between various Michael acceptor electrophiles and indole, [ 35] N ‐methylpyrrole, [36] and a variety of thiophenes [37] have previously been reported, we chose to study reactions between nucleophilic furans and various electrophiles in this project [38–40] . Specifically, the reaction between 2‐methylfuran ( 13 a ) and methyl vinyl ketone ( 14 a ) to form 15 a was initially examined (Table 1).…”
Section: Figurementioning
confidence: 99%
“…Arai et al accomplished halogen-bond-assisted asymmetric Mannich reactions using chiral XB catalysts derived from cinchona alkaloids ( Figure 1 a) [ 17 , 18 ]. Although four more chiral XB catalysts were reported afterwards [ 19 , 20 , 21 , 22 , 23 ], all the structures of chiral XB catalysts are limited to those containing a sp 2 -hybridized carbon–iodine (C sp2 –I) moiety. Besides, the current chiral XB catalysts are based on very few core structures, resulting in less developed asymmetric reactions, and thus a need for novel motifs.…”
Section: Introductionmentioning
confidence: 99%